Three-field lymph node dissection in treating the esophageal cancer - Shang, Qi-Xin; Chen, Long-Qi; Hu, Wei-Peng; Deng, Han-Yu; Yuan, Yong; Cai, Jie (Journal of Thoracic Disease, 2016)
There are many controversies in lymphadenectomy for thoracic esophageal cancer, and whether 3-field lymphadenectomy or 2-field lymphadenectomy is better have still been in doubt. The aim of this article is to review the role of the lymph node dissection by introducing the merits and demerits in 3-field lymphadenectomy, and the development in lymphadenectomy’s selection, treatment and diagnosis. All the literatures related to esophageal lymphadenectomy and minimally invasive surgery (MIE) were searched in Pubmed database and the cross references were added and reviewed to complete the reference list. Several researches elucidated that better overall survival (OS) in patients with esophageal cancer after 3-field lymphadenectomy had been reported worldwide, and 3-field lymphadenectomy is more suitable for treating esophageal cancer with cervical and/or upper mediastinal lymph nodes metastasis than 2-field lymphadenectomy regardless of the tumor’s histology and location. Many approaches based on the characteristics of esophageal cancer lymph node metastasis are taken to improve the accuracy of 3-field lymphadenectomy and decrease the postoperative morbidity and mortality, while every approach needs further studies to demonstrate its feasibility. The benefits of the recently rapid-developed techniques performed in treating esophageal cancer: the MIE and the robotic-assisted thoracoscopic esophagectomy are illuminated as well, and both of them are technically safe and feasible for esophageal cancer, whereas further evaluations are still necessary.